Stress Testing Financial Systems : What to Do When the Governor Calls - Hilbers, Paul (IMF Working Papers; Working Paper ;, 2004)
Stress testing is becoming a widely used tool to assess potential vulnerabilities in a financial system. This paper is intended to answer some of the basic questions that may arise as part of the process of stress testing. The paper begins with a discussion of stress testing in a financial system context, highlighting some of the differences between stress tests of systems and of individual portfolios. The paper provides an overview of the process itself, from identifying vulnerabilities, to constructing scenarios, to interpreting the results. The experience of the IMF in conducting stress testing as part of the Financial Sector Assessment Program (FSAP) is also discussed.